Using SmartSketch - Cheng, Ron. (Clifton Park, NY : Thomson/Delmar Learning, 2005)
"SmartSketch is a 2D computer-aided design tool for constructing 2D schematic diagrams as well as precision engineering drawings."--Pref.
"OnWord Press"--Cover.
Includes index.
All age.
Keywords: SmartSketch (Electronic resource); Computer graphics; Engineering graphics; Computer-aided design